2021
DOI: 10.1021/acsami.1c04828
|View full text |Cite
|
Sign up to set email alerts
|

Significantly Enhanced Thermoelectric Performance of Graphene through Atomic-Scale Defect Engineering via Mobile Hot-Wire Chemical Vapor Deposition Systems

Abstract: Over the years, numerous studies have attempted to develop two-dimensional (2D) materials for improving both the applicability and performance of thermoelectric devices. Among the 2D materials, graphene is one of the promising candidates for thermoelectric materials owing to its extraordinary electrical properties, flexibility, and nontoxicity. However, graphene synthesized through traditional methods suffers from a low Seebeck coefficient and high thermal conductivity, resulting in an extremely low thermoelec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…In our previous work, we reported that HATB domains can induce effective phonon scattering; consequently, the k of graphene grown on polycrystalline Cu showed a significantly low value (∼381 W m −1 K −1 at 350 K), which is lower than that of conventional polycrystalline graphene (∼952 W m −1 K −1 at 350 K). 21,35 In contrast, the measured k of graphene grown on Cu/Ni (111) was ∼1348 W m −1 K −1 at 350 K, which is a remarkable improvement compared to that on polycrystalline Cu (∼381 W m −1 K −1 ) and Cu (111) (∼646 W m −1 K −1 ). This result provides evidence of the crystallinity enhancement for graphene grown on Cu/Ni (111) in terms of structural defects which can cause phonon scattering.…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…In our previous work, we reported that HATB domains can induce effective phonon scattering; consequently, the k of graphene grown on polycrystalline Cu showed a significantly low value (∼381 W m −1 K −1 at 350 K), which is lower than that of conventional polycrystalline graphene (∼952 W m −1 K −1 at 350 K). 21,35 In contrast, the measured k of graphene grown on Cu/Ni (111) was ∼1348 W m −1 K −1 at 350 K, which is a remarkable improvement compared to that on polycrystalline Cu (∼381 W m −1 K −1 ) and Cu (111) (∼646 W m −1 K −1 ). This result provides evidence of the crystallinity enhancement for graphene grown on Cu/Ni (111) in terms of structural defects which can cause phonon scattering.…”
mentioning
confidence: 93%
“…A promising strategy to overcome the obstacles of the aforementioned approaches is to locally recrystallize the pregrown graphene nanograins unidirectionally from one edge to the other edge during growth before all the nanograins globally coalesce into a single film, as in the Czochralski method and floating-zone recrystallization, which have been known to form single crystals of three-dimensional materials. However, this method is challenging for a conventional CVD system because it cannot separate nucleation from subsequent growth at the fixed temperature of the whole volume in the growth chamber. Our invention of a new CVD system by providing additional local heat energy with a mobile hot wire (MHW) over the growth substrate whose temperature is only high enough for nucleation and not for growth can enable this strategy. In our previous work, we reported MHW-CVD growth of defect-controlled single-layer graphene on polycrystalline Cu , and Cu–Ni alloy substrates . During graphene growth in the MHW-CVD system, the pregrown graphene nanograins with random orientation on a catalytic metal substrate rotate and merge with each other along a specific orientation because the grains can align to form energetically stable bonds with neighboring grains depending on the growth parameters, such as the substrate temperature ( T sub ), hot-wire scan speed ( V w ) and temperature ( T w ), and flow rate of the carbon feedstock.…”
mentioning
confidence: 99%
See 3 more Smart Citations